2021
DOI: 10.1061/(asce)hy.1943-7900.0001842
|View full text |Cite|
|
Sign up to set email alerts
|

How Large Immobile Sediments in Gravel Bed Rivers Impact Sediment Transport and Bed Morphology

Abstract: A common approach used to mitigate riverbank erosion and maintain watercourse alignments has been through the application of riprap or larger, more stable particles, to channel boundaries along reaches of interest. Very often, however, these large particles become dislodged from their 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…However, with increasing boulder concentration, we expect channel slope to decrease as the channel self-organizes a new bed largely composed of boulders such that boulders are no longer significant roughness elements on the bed. This situation is equivalent to the role of boulder spacing, shown by flume experiments, to strongly influence grade conditions (McKie et al, 2021). Each boulder generates a unique zone susceptible to flow reversals and enhanced turbulence (Papanicolaou & Tsakiris, 2017).…”
mentioning
confidence: 94%
“…However, with increasing boulder concentration, we expect channel slope to decrease as the channel self-organizes a new bed largely composed of boulders such that boulders are no longer significant roughness elements on the bed. This situation is equivalent to the role of boulder spacing, shown by flume experiments, to strongly influence grade conditions (McKie et al, 2021). Each boulder generates a unique zone susceptible to flow reversals and enhanced turbulence (Papanicolaou & Tsakiris, 2017).…”
mentioning
confidence: 94%
“…In a series of experiments by McKie et al, the various distance effects of stabilized large sediment particles on the bed and transported sediment sizes in gravel-bed rivers were investigated. The results reflected that reducing the spaces between the particles made the transported and bed sediment sizes coarser [12]. White and Nelson used a sinusoidal flume with constant flow rates to study the mechanisms influencing sediment sorting patterns in a channel bed.…”
Section: Introductionmentioning
confidence: 99%
“…The significant disparity between the predicted f values obtained from the two predictors (Fig. 4a) can be attributed to surface water variations influenced by abrupt changes in bed slope (see S in Table 1), the distribution of gravel, cobbles, and boulders elements (Okhravi and Gohari, 2020), the shape and position of large cobbles and boulders (Hodge et al, 2020;McKie et al, 2021;Nicosia et al, 2023), and their protrusion from the channel bed (Hodge et al, 2020). The study by Ferro (2018a) on the potential application of the self-similarity hypothesis to flowresistance laws demonstrated that flow resistance depends on the Reynolds, Froude, and Shields (1936) numbers.…”
Section: Discussionmentioning
confidence: 99%